Triazole-Estradiol Analogs Induce Apoptosis and Inhibit EGFR and Its Downstream Pathways in Triple Negative Breast Cancer - Felix Acheampong; Trevor Ostlund; Emily Hedge; Jacqueline Laddusaw; Faez Alotaibi; Yaseen A. M. M. Elshaier; Fathi Halaweish (Molecules, 2025)
Triple negative breast cancer, TNBC, is a difficult disease to treat due to relapse and resistance to known therapies. Epidermal growth factor receptor (EGFR), a tyrosine kinase responsible for downstream signaling leading to cell growth and survival, is typically overexpressed in TNBC. Our previous work has detailed the synthesis of triazole-estradiol derivatives as inhibitors of EGFR and downstream receptors, and this work continues that discussion by evaluating them in EGFR-dependent TNBC cell models MDA-MB-231 and MDA-MB-468. Compound Fz25 was cytotoxic against both MDA-MB-231 and MDA-MB-468 cell lines, yielding IC50 values of 8.12 ± 0.85 and 25.43 ± 3.68 µM, respectively. However, compounds Fz57 and Fz200 were potent against only MDA-MB-231 cells, generating IC50 values of 21.18 ± 0.23 and 10.86 ± 0.69 µM, respectively. Pathway analyses revealed that Fz25, Fz57 and Fz200 arrested the G0/G1 phase of the cell cycle and concomitantly suppressed cell cycle regulators, cyclin D1, cyclin E and Dyrk1B in MDA-MB-231 cells. Additionally, all compounds inhibited EGFR and its downstream signaling pathways—extracellular receptor kinase (ERK) and the mammalian target of rapamycin (mTOR)—in a dose-dependent manner. Furthermore, Fz25, Fz57 and Fz200 induced apoptosis in MDA-MB-231 cells by modulating morphological changes, including chromatin condensation, and attenuating the levels of cytochrome c, APAF1, caspases-3 and -9 as well as cleaved PARP. Of these compounds, only Fz25 showed overall satisfactory ADMET properties in silico. Similarly, Fz25 showed suitable binding parameters explored using molecular dynamic simulations in silico. These findings suggest that Fz25 warrants further preclinical and clinical investigations as a new generation of triazole congeners with significant potency in EFGR-dependent TNBC.